Conversion from twice‐daily to once‐daily tacrolimus formulation in pediatric liver transplant recipients – a long‐term prospective study. (27th September 2017) - Quintero, Jesús; Juampérez, Javier; Ortega, Juan; Molino, José A.; Castells, Lluis; Bilbao, Itxarone; Rodrigo, Carlos; Charco, Ramón
Summary: To assess the safety and efficacy of conversion from twice‐daily tacrolimus to once‐daily tacrolimus in pediatric liver transplant recipients. Conversion from twice‐daily to once‐daily tacrolimus was made in stable pediatric liver transplant recipients. Doses and serum levels of tacrolimus, liver, and renal function were recorded on the day before the conversion and at days 5, 30, 90, and 180 postconversion. Patients were controlled every 2–3 months thereafter. Fifty‐five patients were enrolled in the study. The mean age at conversion was 10.2 ± 3.6 years. The mean tacrolimus trough level was 4.7 ± 1.9 ng/dl preconversion, followed by a significant decline to 4.2 ± 1.7 30 days after the switch ( P < 0.004). Mean daily tacrolimus dose was 0.09 ± 0.046 mg/Kg preconversion with a significant increase to 0.11 ± 0.060 3 months postconversion ( P < 0.001). Fifteen patients with calculated glomerular filtration rate between 60 to 80 ml/min/m 2 preconversion showed a significant improvement one and 3 years after the switch (73 ± 4.1, 83 ± 4.3 and 90.3 ± 7.3 ml/min/m 2, respectively ( P < 0.001). The mean follow‐up was 5.2 ± 2.4 years. Conversion to once‐daily tacrolimus is safe and effective in a cohort of stable pediatric liver transplant patients.